2017
DOI: 10.3382/ps/pew381
|View full text |Cite
|
Sign up to set email alerts
|

In ovo supplementation of probiotics and its effects on performance and immune-related gene expression in broiler chicks

Abstract: Probiotics are live, nonpathogenic microorganisms known to have a positive effect on the host by improving the natural balance of gut microbiota. The objective of this study was to determine the effects of administering probiotics (Primalac W/S) in ovo on hatchability, early post-hatch performance, and intestinal immune-related gene expression of broiler chicks. At embryonic day eighteen, 360 Cobb 500 eggs were injected with sterile water (sham), 1 × 105, 1 × 106, or 1 × 107 (P1, P2, and P3 respectively) probi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
57
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 36 publications
11
57
1
3
Order By: Relevance
“…In this experiment, in ovo supplementation of probiotics had no effect on hatchability further corroborating our previous findings [22,26]. Very few studies have been published regarding the concept of administrating probiotics via the in ovo route.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…In this experiment, in ovo supplementation of probiotics had no effect on hatchability further corroborating our previous findings [22,26]. Very few studies have been published regarding the concept of administrating probiotics via the in ovo route.…”
Section: Discussionsupporting
confidence: 80%
“…A reduction in intestinal colonization by pathogenic bacteria may have eliminated the need for the induction of these genes. Several studies have demonstrated the ability of probiotics to modulate the levels of several cytokines; however, discrepancies have been noted due to differences in the bacterial strains, combinations of probiotic strains, and presence or absence of a challenge [15][16][17]22]. Further supporting our findings, many reports have noted decreases in immune-related factors.…”
Section: Edens Et Al Compared the Hatchability Of Broiler Embryos Insupporting
confidence: 79%
See 3 more Smart Citations